2009
DOI: 10.1016/j.jcf.2009.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Non-invasive liver elastography (Fibroscan) for detection of cystic fibrosis-associated liver disease

Abstract: Fibroscan is an objective measure and is easy to perform in CF patients, even in children and could provide a valuable tool to detect, and quantify CFLD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
67
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(76 citation statements)
references
References 24 publications
8
67
1
Order By: Relevance
“…The TE was comparable to the ultrasound scoring system in evaluating for CFLD, sensitivity of 63% and specificity of 87%. TE was also comparable to the ultrasound scoring system in detection of hepatic fibrosis (30). Similarly, another study found that elasticity values of controls, pancreatic sufficient CF patients and pancreatic insufficient CF patients with an ultrasound showing either normal or homogenously hyperechoic livers, were comparable and significantly lower than in CF patients with heterogenous, nodular livers or with evidence of portal hypertension on ultrasound (P <0.002).…”
Section: Cystic Fibrosismentioning
confidence: 70%
See 1 more Smart Citation
“…The TE was comparable to the ultrasound scoring system in evaluating for CFLD, sensitivity of 63% and specificity of 87%. TE was also comparable to the ultrasound scoring system in detection of hepatic fibrosis (30). Similarly, another study found that elasticity values of controls, pancreatic sufficient CF patients and pancreatic insufficient CF patients with an ultrasound showing either normal or homogenously hyperechoic livers, were comparable and significantly lower than in CF patients with heterogenous, nodular livers or with evidence of portal hypertension on ultrasound (P <0.002).…”
Section: Cystic Fibrosismentioning
confidence: 70%
“…CFLD may show patchy fibrotic changes early on in the disease process, so liver biopsy may miss a diseased region due to sampling error. Witters et al (30) evaluated sixty-six pediatric cystic fibrosis patients with TE and compared them to a control group of healthy children. Liver disease was defined clinically based on the presence of hepatomegaly or splenomegaly and biochemically based on elevated liver function tests (1.5 times the upper limit of normal for age) for 3-6 months.…”
Section: Cystic Fibrosismentioning
confidence: 99%
“…Liver stiffness as correlate of hepatic fibrosis has been investigated also using a different technique, which is the transient elastography [25,26]. Both the latter studies and our investigation respond to the need for non-invasively staging of hepatic fibrosis in CFLD.…”
Section: Sign Of Pancreatic/liver Involvementmentioning
confidence: 74%
“…In 2010, Menten et al [12] studied FibroScan measurements in 134 CF patients and found that the FibroScan values were significantly elevated in patients with sonographic evidence of fibrosis. Witters et al found a significant elevation in the FibroScan values of 66 CF patients with liver disease, as defined by clinical, laboratory, or sonographic markers [13].…”
Section: Discussionmentioning
confidence: 99%
“…Transient elastography has been used for several years in adults with chronic liver disease to detect cirrhosis and to evaluate the complications of portal hypertension [8,9]. In adults and in children [10][11][12][13], transient elastography is being evaluated for cystic fibrosisassociated liver disease and for the detection of esophageal varices in other causes of cirrhosis in children [14]. The goal of this study was to investigate the relationship between transient elastography values and the presence of esophageal varices in CF patients with liver disease.…”
Section: Introductionmentioning
confidence: 99%